1977
DOI: 10.1136/jnnp.40.12.1220
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal bleeding in haemophilia: successful treatment with factor VIII concentrate.

Abstract: SUMMARY A severely affected haemophilic boy became tetraparetic as a result of a spontaneously occurring intraspinal haematoma. Myelography defined the extent of the lesion and showed it to be extradural in site. Infusion of large doses of factor VIII concentrate led to dramatic improvement and avoided the need to operate.Intraspinal bleeding in haemophilia is extremely rare and recovery is even rarer. To date 14 cases have been recorded, and 11 of these have died. We report here a severely affected haemophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…In the sagittal T2-weighted cervical MRI, the hematoma from C5 to midthoracic level, was hyperintense and mainly posteriorly located in the thoracic and thoracolumbar level. This is compatible with the timing of the imaging (6 th day after trauma and hemorrhage)[9,10] and is postulated to occur because of methemoglobin formation [11]. In the T1-weighted axial MRI scan of the lower thoracic region, areas of hyperintensity in the periphery of the hematoma were seen, suggesting methemoglobin formation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the sagittal T2-weighted cervical MRI, the hematoma from C5 to midthoracic level, was hyperintense and mainly posteriorly located in the thoracic and thoracolumbar level. This is compatible with the timing of the imaging (6 th day after trauma and hemorrhage)[9,10] and is postulated to occur because of methemoglobin formation [11]. In the T1-weighted axial MRI scan of the lower thoracic region, areas of hyperintensity in the periphery of the hematoma were seen, suggesting methemoglobin formation.…”
Section: Discussionsupporting
confidence: 68%
“…The limited available literature mainly addresses the management of spinal epidural hematoma in the hemophiliacs [13-15,9]. Schmitz et al [16] has reported his survey of treatment and outcome in hemophilic patients with spinal epidural hematoma from 1977 to 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Such bleeds have been described in patients of all ages [ 1], but predominately in infants and children when due to inherited bleeding disorders [ 4]. As expected, patients with severe haemophilia A or B are most often affected, and neurological sequelae [ 5] or death [ 2] often ensue unless effective replacement therapy can be administered.…”
Section: Discussionmentioning
confidence: 99%
“…However, more and more cases are reported where patients with Haemophilia could be treated successfully with conservative measures ( Table 1). Even a spastic tetraparesis could be improved with replacement therapy [19]. Table 1 gives a survey of treatment and outcome in Haemophilia in the last 20 years.…”
Section: Discussionmentioning
confidence: 99%